A case report of pulmonary artery sling and situs inversus incompletes. Issue 3 (22nd January 2021) - Xu, Yingchun; Xu, Dan; Cheng, Beilei; Tang, Lanfang; Chen, Zhimin; Du, Lizhong
Abstract: Rationale: Pulmonary artery sling (PAS) is a rare congenital anomaly. Associated airway anomalies and/or those of the cardiovascular system are present in about half the patients. Situs inversus is a rare disease in which organs of the chest and/or abdomen are arranged in a mirror image reversal of their normal position. Herein, we report a rare case of pulmonary artery sling and situs inversus incompletus, which has not yet been reported. Patient concerns: A 10-year-old girl was admitted because of heart murmur for more than 9 years. On physical examination, the second heart sound was prominent, and a grade 2/6 systolic murmur was heard at the left mid-sternal border. Echocardiography revealed PAS and atrial septal defect (8.6 mm). A chest computer tomography angiograph demonstrated that she had lung inversus, right aortic arch, and right lung hypoplasia in addition to PAS, with a normal positioning of the heart. The PAS intersected and twisted across the bronchus, which was obviously narrowed. The PAS was type II B, since the carina was at the T6 level without a separate right upper lobe bronchus. Diagnoses: Her final diagnosis was that of PAS, tracheal stenosis, situs inversus incompletus, right lung hypoplasia, right aortic arch, ASD and PDA. Interventions: She underwent one-stage total correction for her initial cardiovascular defects through median sternotomy under cardiopulmonary bypass support. Outcomes: She had an uneventful recovery and completely healthy following the procedure. Lessons: A thorough examination before PAS surgery was essential in discovering and carefully evaluating complicated heart and lung anomalies.